The impact of CLIL on the acquisition of L2 competences and skills in primary education - Nieto Moreno de Diezmas, Esther (International Journal of English Studies, 2016)
The aim of this paper is to provide new evidence on the effectiveness of Content and Language Integrated Learning (CLIL) in the acquisition of English language competences (reading, writing, listening and spoken production and interaction) compared to traditional learning of English as a foreign language (EFL) in primary school settings. To do so, results of CLIL and non-CLIL learners enrolled in the 4 th year of primary education (9-10-year-olds) were examined and contrasted. Findings showed that the only communicative competence in which differences in favour of CLIL students were significant was spoken production and interaction. However, significant differences have also been detected in the following indicators: “preparing an outline before writing” (writing), “understanding space-time relations” (reading), and “global comprehension” and “identification of details” (listening). The confined effectiveness of CLIL may be due to the limited time of extra exposure to English, the young age of participants and the absence of any selection process for CLIL learners.